Extra Cellular Matrix Deposition and Assembly in Dermis Spheroids - Rescigno F; Ceriotti L; Meloni M (Dove Medical Press, 2021)
Francesca Rescigno, Laura Ceriotti, Marisa Meloni VitroScreen, In Vitro Innovation Center, Milan, ItalyCorrespondence: Francesca RescignoVitroScreen, In Vitro Innovation Center, via Mosè Bianchi, 103, Milan, 20149, ItalyEmail francesca.rescigno@vitroscreen.comObjective: Dermis spheroids from different donors (40 and 50 years old) were developed from primary fibroblasts to demonstrate their capacity to synthetize and organize the main dermal structural components when cultured in 3D microenvironment, forming endogenous de novo ECM according to their potential metabolic activity.Methods: Dermis spheroids were produced from primary human dermal fibroblasts at early passages in hanging drop culture system. Dermis models were characterized in terms of spheroid diameter, PICP release, collagen III and CD44 expression.Results: An increase of collagen III synthesis (101%) was found in the young donor compared to the old donor (23.5%) after seven days of culture by immunofluorescence. The progressive ECM assembly over the time and dermis maturation was showed by Masson's trichrome staining and by immunofluorescence for collagen III and CD44; both molecules significantly accumulated in the dermal compartment from day seven to day 10 of culture with a global decrease for both spheroid models after 21 days of culture.Conclusion: Our results showed that specific culture conditions in the 3D scaffold-free microenvironment allowed the physiological and progressive ECM assembly of miniaturized dermis models reflecting phenotypic profile features of "young" and "old" native tissue from which cells were isolated with a potential application to personalized care approaches in dermatological research on aging processes and medicine.Keywords: 3D culture, dermis, scaffold-free spheroids, intrinsic aging, extracellular matrix, tissue remodeling